Everyone wants something better than ΛCDM - Michael S. Turner (Proceedings of the National Academy of Sciences, 2026)
The current cosmological paradigm, ΛCDM, is characterized by its expansive description of the history of the Universe, its deep connections to particle physics and the large quantities of data that support it. Nonetheless, ΛCDM’s critics argue that it has been falsified or must be discarded for various reasons. Critics and boosters alike do agree on one thing: It is not the final cosmological theory and they are anxious to see it replaced by something better! I review the status of ΛCDM, provide my views on what “better” might look like, and discuss the role that the “Hubble tension” might play in moving beyond ΛCDM.